Multiple Vulvar Giant Fibroepithelial Polyps: A Rare Case Occurrence - Andi Kurniadi; Andi Rinaldi; Herry Yulianti; Abi Ryamafi Bazar; Rose Dita Prasetyawati; Kevin Dominique Tjandraprawira (Hindawi Limited, 2022)
Fibroepithelial polyps or acrochordons are benign skin tumors of mesenchymal and ectodermal origin. They are seen in 25% of the population, and their frequency increases with age. They are often found in areas with skin folds, such as the neck, axilla, submandibular, or inguinal region. However, they can also be located in the genital tract. Hormone imbalances may facilitate the development of fibroepithelial polyp s (e.g., high levels of estrogen and progesterone during pregnancy). Larger lesions are likely to arise from the proliferation of mesenchymal cells within the hormonally sensitive subepithelial stromal layer of the lower. Generally, their size does not exceed 5 millimeters. We present a 28-year-old patient with multiple giant fibroepithelial polyps with size of 20×12×8 cm and 9×4×2 cm, located on both sides of her vulva. Herein, we presented our patient along with the review of current literature pertaining to the diagnosis and the treatment of fibroepithelial polyps (FEPs) and the factors leading to excessive growth.